PARTISIPASI MASYARAKAT DALAM PROGRAM BANTUAN KREDIT MIKRO NAGARI MELALUI POLA BAITUL MAAL WAT TAMWIL - Primadini Putri (Jurnal Kebijakan Publik, 2010)
The giving of autonomy to a region was a trial to cover the development in every sector. Havingautonomy, each region has right to arrange its own mission and control the development in its region byusing its own budget so that the regional and sectoral development could be balance by increasing theparticipation of society. The development is natural process in getting thepurpose of the country, the welfarein whole soceity. The welfare was indicated by increasing income. In creasing income was related to increasingproductivity. It natural process can be done if the development assumptions whether the job opportunity orparticipation applied well. Everybody has equal productivity and rational behaviour.